Evaluation of the fractionation of ten medicines in tablets under three methods in Costa Rica - Baudrit Carrillo, Olga (2017)
To obtain the correct dose it was sometimes necessary to split tablets. Some organizations have developed guides in order to verify the quality of the tablets with functional score and their fragments. The objective of this work was to evaluate the fractionation of tablets in halves, performed with three methods and applied to ten medicines used in pathologies of epidemiological relevance in Costa Rica. For each medicine, 60 participants fractionated a tablet once with splitter, knife and hand. The errors produced in the fractionation was determined. The tablet breaking force and the uniformity of mass of whole tablets were verified and the test of uniformity of mass and the percentage of loss of mass was applicate to tablets halves. The results showed that 98% of the whole tablets were in the expected range of Percentage deviation of mass average. No pattern linked the breaking force with the results of tablets halves. A high number of errors in the fractionation were associated with the knife. About tablets halves, the splitter showed the better accuracy for split, and the good results in percentages of loss of mass were evidenced for the fractionation with hand. The fractionation showed a global waste of 46% of 1,800 tablets available for the study. Atenolol and warfarin sodium have the higher levels of waste, which draw attention due to their high consumption associated with to the epidemiological profile of population. These findings should not be extrapolated to other unanalyzed batches and neither to other drugs.